The effect of social and environmental disclosure on companies’ market value - Husser, Jocelyn; Evraert-Bardinet, Frédérique (Management international / International Management / Gestiòn Internacional)

(untitled) (HEC Montréal, 2014)
The research looks at the relationship between market value, accounting fundamentals and companies’ Corporate Social Responsibility (CSR) and Sustainable Development (SD) disclosures for the years 2007-2008. This article uses social and environmental scores derived from a structural analysis chart based on 120 companies’ reports. The results show that investors measure a company’s short-term performance using information about the quality of the company’s environmental management. At the same time, a company’s social disclosure concerning the quality of employee management influences short and long-term performance.